Palm Oil Exports Increased Due To Rupiah Depreciation, International Price Factors And Government Regulations - Reni Rafki; Rafnelly Rafki; Yolanda Oktarina; Nofriadi Nofriadi; Yulasmi (ARRUS Journal of Social Sciences and Humanities, 2023)
Palm oil is a very important export commodity for Indonesia, contributing significantly to the country's economy in terms of both production and export. Fluctuations in the rupiah exchange rate against foreign currencies, especially the US dollar, have been widely studied, which turned out to affect the export of various commodities, including palm oil. However, the linkages to international prices and government regulation have not been studied much. This study aims to examine how much influence international prices, rupiah depreciation, and Indonesian government regulations have on increasing palm oil exports to India. Data collection method through surveys and circulating questionnaires, with a sample of 100 respondents. The analysis method used is multiple linear regression analysis using SPSS. The results of the study obtained based on the partial test (t test) obtained a positive and significant influence between international prices on increasing exports. There is a positive and significant influence between rupiah depreciation and increased exports. There is a positive and significant influence of Indonesian government regulations on increasing exports. The contribution of the percentage contribution of the independent variable of international prices, rupiah depreciation, and Indonesian government regulations to the dependent variable of increasing exports is 0.811 or 81.1%. While the remaining 0.189 or 18.9% was influenced by other variables outside this study.